Adaptive power allocation in cooperative OFDM transmission with three-hop DF relaying - Wang, Jun; Chai, Xiaomeng; Zhang, Xu; Zhang, Zhongshan; Long, Keping (2013 IET International Conference on Information and Communications Technologies : April 27-29, 2013, Beijing, China, 2013)
Adaptive power allocation subject to the total power constraint in an end-to-end cooperative orthogonal frequency Division multiplexing (OFDM) system is studied, with the optimal power allocation in terms of maximizing the sum transmission Rate being derived. The conventional two-hop system model is extended to a three-hop structure in this paper to improve the Wireless coverage. Independent and identically distributed (i.i.d.) sub-channels are assumed in each Decode-and-Forward (DF) relay without considering the effect of inter-relay interference. Relay selection is also performed in the proposed cooperative transmission, and each relay itself decides whether to forward data for the source depending on the quality of the sub-channels. The transmission bottleneck in the conventional two-hop cooperative system can be overcome effectively, especially when the source-to-destination and first-hop relay-to-destination links are both in a deep fading. The proposed theoretical analysis is validated by using simulation, and it's shown that the sum rate of the proposed algorithm is the monotonically increasing function of both the sub-channel numbers and total system power. Numerical results also prove the superiority of the proposed three-hop model over the conventional two-hop system in terms of end-to-end sum data rate.